Analisis Tingkat Pertumbuhan Bank Syariah di Indonesia - Rahma Putri, Deasy Ayu; Rachmawati, Lucky (Jurnal Ekonomika dan Bisnis Islam, 2022)
The Islamic economy in Indonesia continues to grow rapidly. This growth cannot be separated from the role of many institutions that run with sharia principles, especially Islamic banking. This study has the purpose of analyzing the growth rate of Islamic banks in 2017-2019. The method used is Multiple Linear Regression to determine the growth of Islamic banking in Indonesia. This study uses the variables of assets, third-party funds, profit for the year, and financing. This study uses quarterly time-series data from the first quarter of 2017 to the fourth quarter of 2019 and is obtained from the Islamic Banking Statistics data of the Financial Services Authority. The results of this study, namely the variables of assets, financing, profit for the year, and third-party funds affect the growth rate of Islamic banks in Indonesia. Assets and profits for the year have a significant positive effect, while financing and third-party funds have a negative effect on the growth of Islamic banks in the 2017-2019 period. During that period, the growth of Islamic banks in Indonesia fluctuated but growth in each variable increased.